2022
DOI: 10.3389/fenvs.2022.959850
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Foreign Direct Investment and Tourism on Carbon Emission in China

Abstract: The aim of this research is to examine the potential influence of FDI inflows and tourism industry on carbon dioxide emissions in China using System GMM models for a sample period of 1980–2019. Using FMOLS and DOLS models, this research examines the long-term relationship between the variables, as well as the long-term association among components. Co-joining the boards of FMOLS and DOLS models shows a general correlation between the investigation elements and CO2 emissions in China. FDI, tourism sector, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Wang et al [61] used the full modified ordinary least squares (FMOLS) and dynamic normal least squares (DOLS) models and found that FDI, the tourism sector, and environment-friendly electricity were positive contributors towards CO 2 e in China from 1980 to 2019. Mehmood et al [23] examined the relationship of FDI with renewable energy and found a significant decrease in CO 2 e in South Asian countries by using CS-ARDL from 1996 to 2019.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Wang et al [61] used the full modified ordinary least squares (FMOLS) and dynamic normal least squares (DOLS) models and found that FDI, the tourism sector, and environment-friendly electricity were positive contributors towards CO 2 e in China from 1980 to 2019. Mehmood et al [23] examined the relationship of FDI with renewable energy and found a significant decrease in CO 2 e in South Asian countries by using CS-ARDL from 1996 to 2019.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%